Radiocarbon Wiggle-Match Dating in the Intertidal Zone. (2nd January 2019) - Jacobsson, Piotr; Hale, Alex; Hamilton, Derek; Cook, Gordon
ABSTRACT: Radiocarbon wiggle-match dating is a technique that can combine the versatility of radiocarbon dating with chronological information from tree-rings. This makes it useful in contexts where timbers are preserved, but dendrochronological dating is impossible. As intertidal and marine timbers are waterlogged, this can favor their preservation and hence allow wiggle-match 14 C dating, which can be of significant help in deriving relatively precise chronologies for a range of coastal structures. As the technique depends on making multiple radiocarbon measurements towards a single date, efficiency in application is the key and hence a number of practical considerations need to be taken into account in advance of conducting a dating program. This paper discusses some of these practical concerns and reviews them in the context of the intertidal crannogs in the Firth of Clyde on the west coast of Scotland.